A Comprehensive Compact Model for Multilevel Switching in TaOx-Based Memristive 1T-1R Cells - Seokki Son; Ankit Bende; Daniel Schon; Rana Walied Ahmad; Dennis Nielinger; Vikas Rana; Stephan Menzel (IEEE Access, 2025)
Filamentary switching memristive devices based on the valence change mechanism (VCM) are promising for non-volatile memory applications due to their ability to store multiple resistance states within a single device. To facilitate the integration into circuits, this study presents an advanced compact model designed for multilevel switching in the VCM devices serially connected with transistors in a 1T-1R configuration. This model is an extension of the existing JART (Jülich Aachen Resistive Switching Tools) VCM v1b model, by incorporating state-dependent effective thermal resistance ( $R_{th,eff}$ ) based on an electro-thermal continuum model. This enables precise modeling of multilevel behavior and includes the variability in switching cycles to reflect experimental conditions. The validation with TaOx-based VCM devices co-integrated with 180 nm n-MOS transistors demonstrates the model’s accuracy, achieving consistent multilevel programming across 7-states and capturing cycle-to-cycle variability effectively. This model offers a robust tool for designing reliable, high-density multilevel ReRAM memory system.